An Atypical Cause of an Epiglottic Abscess - Muneera Rabeea; Hasan Al Ansari; Amal Al Abdulla (Case Reports in Infectious Diseases)
An epiglottic abscess is a rare complication of acute epiglottitis and is life threatening. We describe a case report of a diabetic adult male, who presented with an epiglottic abscess. Culture results showed Aeromonas hydrophila, an organism rarely reported as a cause of acute epiglottitis. Early recognition can be lifesaving.